The impact of the joint audit and electronic disclosure approach on the market value of companies registered in the Saudi financial market - elsayed Metwaly ATIA, Metwaly (Journal of Research in Finance and Accounting, 2023)
The objective of this study is to obtain a practical evidence from the Saudi business environment for the impact of both joint audit and online disclosure on the market value of listed firms in the Saudi capital market. The study used content analysis to examine the annual reports for a sample of (90) listed firms in the Saudi stock market, during the period from 2018 to 2021, with a total of (360) observations to test the study hypotheses. The results of the study indicate a positive and significant impact for joint audit on the firms’ market value. The level of online disclosure also significantly affects the firms’ market value.. Based on these results, the study recommends that the Saudi capital market should adopt an online disclosure guidelines for listed firms, and to oblige firms to follow these guidelines when publishing their online information, additionally listed firms should depend on joint auditing to audit their annual reports, as this will positively impact their market value, as this will improve the disclosure of both financial and non-financial information, and enhances transparency, relevance and timeliness of financial reports. This would also improve the accuracy, objectivity and confidence in the firms’ financial reports.